2017
DOI: 10.3390/s17071650
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Differential Measuring Method: Application in Microstrip Sensors Developing

Abstract: Electromagnetic radiation is energy that interacts with matter. The interaction process is of great importance to the sensing applications that characterize material media. Parameters like constant dielectric represent matter characteristics and they are identified using emission, interaction and reception of electromagnetic radiation in adapted environmental conditions. How the electromagnetic wave responds when it interacts with the material media depends on the range of frequency used and the medium paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Planar sensors are of special interest as their low-profile is compatible with many applications, where bulk sensors (e.g., cavity sensors or waveguide-based sensors [1,2], among others) may find a severe limitation, e.g., conformal sensors [3], wearable sensors [4], submersible sensors [5], integrated sensors [6], lab-on-a-chip sensors [7], microfluidic sensors [8][9][10][11], etc. On the other hand, despite the fact that non-resonant planar sensors operating at microwave frequencies have been reported [12][13][14], the combination of sensor size and performance (sensitivity) of resonant-type sensor is difficult to achieve with non-resonant methods. Finally, to end this introductory section, let us mention that although probably most planar microwave resonant sensors have been devoted to material characterization (the main interest in this review paper, to be discussed in detail later), there are many reported realizations focused on motion control applications (linear and angular displacement and velocity measurements) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Planar sensors are of special interest as their low-profile is compatible with many applications, where bulk sensors (e.g., cavity sensors or waveguide-based sensors [1,2], among others) may find a severe limitation, e.g., conformal sensors [3], wearable sensors [4], submersible sensors [5], integrated sensors [6], lab-on-a-chip sensors [7], microfluidic sensors [8][9][10][11], etc. On the other hand, despite the fact that non-resonant planar sensors operating at microwave frequencies have been reported [12][13][14], the combination of sensor size and performance (sensitivity) of resonant-type sensor is difficult to achieve with non-resonant methods. Finally, to end this introductory section, let us mention that although probably most planar microwave resonant sensors have been devoted to material characterization (the main interest in this review paper, to be discussed in detail later), there are many reported realizations focused on motion control applications (linear and angular displacement and velocity measurements) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach for sensing using a harmonic signal is phase-variation [43][44][45][46][47][48][49][50]. Phase-variation sensors are especially suited for material characterization, including dielectric constant measurements, determination of material composition, and defect detection, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Also, microwave structures can be readily implemented in the integrated circuits, which have become a favourable platform due to their constantly decreasing cost. As such, microwave sensors have found numerous applications including permittivity sensing [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], strain and displacement sensing [ 16 , 17 , 18 , 19 , 20 ], detection of biomolecules [ 21 ], glucose monitoring [ 22 , 23 ], dielectric spectroscopy for food quality control [ 24 , 25 ], gas sensing [ 26 , 27 , 28 ], and concentration measurements of liquid solutions [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The operating principles of the proposed microwave sensors predominantly rely on the resonance concept [ 4 , 5 , 6 , 7 , 9 , 10 , 12 , 14 , 15 , 16 , 19 , 20 , 21 , 23 , 29 ], however there are also structures based on transmission line [ 1 , 2 , 18 , 26 , 27 , 28 ] and capacitive methods [ 13 , 17 , 22 ], as well as on more peculiar phenomena such as energy tunneling [ 3 , 11 ] and metasurfaces [ 8 ]. Besides split ring resonators (SRR) [ 4 , 9 , 14 , 15 , 16 , 19 , 20 , 21 ], which have been widely exploited in resonant-type sensors, there have also been proposed sensors with cavity [ 6 , 29 ] and stepped impedance resonators (SIR) [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation